Hepcidin determination in dried blood by microfluidic LC–MS/MS: comparison of DBS and volumetric absorptive microsampling for matrix effect and recovery. (November 2015) - Houbart, Virginie; Cobraiville, Gaël; Servais, Anne-Catherine; Napp, Aurore; Merville, Marie-Paule; Fillet, Marianne
Background: Dried blood analysis experiences a growing interest due to practical, ethical and financial advantages compared with classical wet plasma or serum analysis. Besides classical DBS, new alternatives are commercialized as volumetric absorptive microsampling (VAMS) that are expected to overcome hematocrit influence.Results: The feasibility of hepcidin (a peptide hormone) extraction and determination from DBS and VAMS blood sampling was investigated. Experimental design was used to determine the optimal extraction conditions. Matrix effect and extraction recovery were studied and a special attention was paid to phospholipid removal.Conclusion: The data suggest that the combination of VAMS and phospholipid removal plates provides low matrix effect and high sensitivity, and constitutes an easy and promising protocol for hepcidin analysis.